Development of Modified Grouting Material and Its Application in Roadway Repair Engineering. (4th March 2021) - Yu, Yang; Qin, Zhengyuan; Wang, Xiangyu; Zhang, Lianying; Chen, Dingchao; Zhu, Siyu
Abstract : It is very extraordinary for the success of coal mine roadway grouting with the following factors of high early strength, good fluidity, and convenient pumping, but the existing grouting materials make it difficult to achieve the above characteristics at the same time. Therefore, a modified grouting material is developed, which is composed of two kinds of dry materials A and B, which are mixed with water and in equal amounts. The physical and mechanical properties of modified grouting materials under different ratios were tested by laboratory orthogonal test, and the optimal ratio of grouting materials and additives was obtained: (1) the water-cement ratio is 0.8 : 1; (2) base material: the mass ratio of cement, fly ash, bentonite, and water is 1 : 0.3 : 0.1 : 1.44; (3) admixture: the mass ratio of water reducer C, accelerator D, and retarder E is 1.5% : 0.05% : 0.3%. The basic properties of the modified grouting materials were studied from the aspects of slurry flow state, diffusion range, and grouting parameters by using the numerical simulation method, and the reinforcement mechanism of slurry to the broken surrounding rock properties of the roadway was revealed: (1) the grouting pressure is the main factor affecting the slurry diffusion radius; (2) the mechanical properties of the roadway surrounding rock are improved, the plastic zone and deformation of surrounding rock are reduced, and the active support function of the anchor and cable is enhanced through grouting reinforcement; (3) the control effect of the roadway is improved, and the balanced bearing with anchorage structure of the roadway surrounding rock is realized through grouting reinforcement. On this basis, the modified grouting material is applied to roadway repair and reinforcement engineering practice. The field monitoring data show that the production practices were guided by roadway repair and reinforcement technology with the modified grouting material, as the core of the roadway surrounding rock control effect is good, and the modified grouting material has a wide range of application prospects.